MAKNA SEMIOTIKA DALAM TRADISI MANDI SAFAR MASYARAKAT MELAYU PULAU PENYENGAT - Nur’Aini Herlina Putri; Isnaini Leo Shanty; Legi Elfitra; Suhardi; Maulida Mustado; Musliha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the semiotic meanings contained in the Safar Bathing Tradition practiced by the Malay community of Penyengat Island. This tradition is a form of oral cultural heritage that is still preserved and contains religious, social, and cultural values. The research used a qualitative descriptive method. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman. The results show that the Safar Bathing Tradition contains iconic, indexical, and symbolic meanings that reflect purification, togetherness, religious devotion, and respect for ancestral heritage.